Effects of Nephrolithiasis on Serum DNase (Deoxyribonuclease I and II) activity and E3 SUMO-Protein Ligase NSE2 (NSMCE2) in Malaysian individuals - Yusof, Faridah; Mehde, Atheer Awad; Mehdi, Wesen Adel; Ahmad Raus, Raha; Ghazali, Hamid; Abdul Rahman, Azlina (Elsevier, 2015)
Objective Nephrolithiasis is one of the most common disorders of the urinary tract. The aim of this study was to examine a possible relationship between DNase I/II activity and E3 SUMO-protein ligase NSE2 in the sera of nephrolithiasis patients to evaluate the possibility of a new biomarker for evaluating kidney damage. Methods Sixty nephrolithiasis patients and 50 control patients were enrolled in a case-control study. Their blood urea, creatinine, protein levels and DNase I/II activity levels were measured by spectrometry. Serum NSMCE2 levels were measured by ELISA. Blood was collected from patients of the government health clinics in Kuantan-Pahang and fulfilled the inclusion criteria. Results The result indicated that mean levels of sera NSMCE2 have a significantly increase (P<0.01) in patients compared to control group. Compared with control subjects, activities and specific activities of serum DNase I and II were significantly elevated in nephrolithiasis patients (P<0.01). Conclusion This study suggests that an increase in serum concentrations of DNase I/II and E3 SUMO-protein ligase NSE2 level can be used as indicators for the diagnosis of kidney injury in patients with nephrolithiasis.